Spatial distribution and determinants of Vitamin A supplementation non-receipt among children aged 6–35 months in Ethiopia: a multiscale geographically weighted regression analysis - Kassaw, Altaseb Beyene; Tareke, Amare Abera; Mankelkl, Gosa; Anbesaw, Tamrat; Gedefie, Alemu; Debash, Habtu; Tamirat, Dawit Tesfa; Abebe, Gashaw (Frontiers in Public Health, 2025)
BackgroundVitamin A supplementation is an important public health intervention strategy to reduce childhood morbidity and mortality. However, in Ethiopia, the coverage remained low with significant regional disparities. Hence, this study aimed to explore the spatial distribution and determinants of not receiving Vitamin A supplements among children aged 6–35 months.MethodsThis study utilized the 2019 Ethiopia Mini Demographic and Health Survey data conducted from March to June 2019. A total weighted sample of 2,540 children aged 6–35 months were included in the analysis. Data was managed and analyzed using STATA version 17, ArcGIS version 10.7.1, SaTScan v10.1, and MGWR version 2.2 software. A spatial autocorrelation analysis was performed to assess whether cases of failed to have Vitamin A supplements were randomly distributed or not. Hotspot analysis was performed to identify high or low prevalence, and ordinary kriging was utilized for interpolation. Furthermore, the Bernoulli-based model was used to identify the most likely clusters of not having Vitamin A supplementation by SaTScan analysis. Finally, the Geographical weighted regression and the Multiscale Geographical weighted regression analysis models were fitted to identify the spatially varying determinants of not receiving Vitamin A supplementation.ResultAs the spatial analysis showed, the distribution of not having Vit-A supplements among children 6–35 months in Ethiopia was spatially varied. Clusters with the highest prevalence were identified in Sidama, Southern Nations, Nationalities, and Peoples’ Region, and some parts of Oromia. The scan statistics recognized a total of 44 primary clusters located in Sidama, Southern Nations, Nationalities, and Peoples’ Region, Southwest Ethiopia, and some parts of Oromia (Relative risk = 1.5, p-value < 0.001). The spatial regression analysis showed that the observed geographical variation of not having a vitamin A supplement was associated with being from an uneducated mother, being from a female household head, being from a poor/poorer household, being the first child, a female child, and a child aged 6–23 months.ConclusionThe study reveals significant geographical variation in the prevalence of not having Vitamin A supplements among children aged 6–35 months in Ethiopia. Sociodemographic factors like being from uneducated mothers, poor households, children aged 6–23, and first-born children were found to be some of the determining factors for the disparity. Hence, the need for region-specific public health interventions is highly encouraged to improve the coverage of vitamin A supplementation in Ethiopia.